Spectral and timing evolution of the bright failed outburst of the transient black hole Swift J174510.8−262411. Issue 4 (13th January 2016) - Santo, M. Del; Belloni, T. M.; Tomsick, J. A.; Sbarufatti, B.; Cadolle Bel, M.; Casella, P.; Castro-Tirado, A.; Corbel, S.; Grinberg, V.; Homan, J.; Kalemci, E.; Motta, S.; et al.
Abstract: We studied time variability and spectral evolution of the Galactic black hole transient Swift J174510.8−262411 during the first phase of its outburst. INTEGRAL and Swift observations collected from 2012 September 16 until October 30 have been used. The total squared fractional rms values did not drop below 5 per cent and quasi-periodic oscillations (QPOs), when present, were type-C, indicating that the source never made the transition to the soft-intermediate state. Even though the source was very bright (up to 1 Crab in hard X-rays), it showed a so called failed outburst as it never reached the soft state. XRT and IBIS broad-band spectra, well represented by a hybrid thermal/non-thermal Comptonization model, showed physical parameters characteristic of the hard and intermediate states. In particular, the derived temperature of the geometrically thin disc blackbody was about 0.6 keV at maximum. We found a clear decline of the optical depth of the corona electrons (close to values of 0.1), as well as of the total compactness ratio ℓh /ℓs . The hard-to-hard/intermediate state spectral transition is mainly driven by the increase in the soft photon flux in the corona, rather than small variations of the electron heating. This, associated with the increasing of the disc temperature, is consistent with a disc moving towards the compact object scenario, i.e. the truncated-disc model. Moreover, this scenario is consistent with the decreasing fractional squared rms and increasing of the noise and QPO frequency. In our final group of observations, we found that the contribution from the non-thermal Comptonization to the total power supplied to the plasma is 0.59^+0.02_-0.05 and that the thermal electrons cool to kTe < 26 keV.